2021
DOI: 10.1073/pnas.2109208118
|View full text |Cite|
|
Sign up to set email alerts
|

Neural mechanisms of deliberate dishonesty: Dissociating deliberation from other control processes during dishonest behaviors

Abstract: Numerous studies have sought proof of whether people are genuinely honest by testing whether cognitive control mechanisms are recruited during honest and dishonest behaviors. The underlying assumption is: Deliberate behaviors require cognitive control to inhibit intuitive responses. However, cognitive control during honest and dishonest behaviors can be required for other reasons than deliberation. Across 58 neuroimaging studies (1,211 subjects), we investigated different forms of honest and dishonest behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 17 publications
(17 reference statements)
1
18
0
Order By: Relevance
“… The new ALE results for spontaneous dishonesty (16 studies) reveal significant activations in the right perigenual anterior cingulate cortex ( x = 4, y = 40, z = 22; peak Z = 4.58) and the right inferior frontal gyrus (i.e., ventrolateral prefrontal cortex; x = 36, y = 22, z = −10; peak Z = 4.35)—virtually the same results as our original publication ( 1 ). …”
supporting
confidence: 74%
See 2 more Smart Citations
“… The new ALE results for spontaneous dishonesty (16 studies) reveal significant activations in the right perigenual anterior cingulate cortex ( x = 4, y = 40, z = 22; peak Z = 4.58) and the right inferior frontal gyrus (i.e., ventrolateral prefrontal cortex; x = 36, y = 22, z = −10; peak Z = 4.35)—virtually the same results as our original publication ( 1 ). …”
supporting
confidence: 74%
“…Finally, in agreement with Zhen and Yu ( 2 ), we don't contest that honesty can be as motivational as dishonesty. On the contrary, we stress, in the original paper ( 1 ), and here again, the neglect of such a research question in the current literature, and call for more research on this motivational dimension, which we believe plays a nonnegligible role in both honesty and dishonesty.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Using activation likelihood estimation (ALE) metaanalysis ( 3 ), Sai et al. report that, in comparison with spontaneous truth telling, spontaneous dishonesty shows consistent activations uniquely in the perigenual anterior cingulate cortex (pgACC) ( 4 ). The authors argue that the motivational/volitional dimension is central to deliberate dishonesty.…”
mentioning
confidence: 99%
“…Furthermore, the repeated use of drugs may lead to dysfunction in the cognitive mechanisms related to decisionmaking (Verdejo-Garcia, Chong, Stout, Yücel, & London, 2018). Moreover, a study investigated several honest and dishonest behaviors and demonstrated that many brain regions previously implicated in dishonesty may be related to general cognitive processes (Sai et al, 2021). On the other hand, it is unclear when to test politicians and their potential decisionmaking processes.…”
Section: Abstract Introductionmentioning
confidence: 99%